Effect of Temperature on Slagging During Solid Refuse-Derived Fuel Combustion with Dolomite Additives: Pengaruh Temperatur Terhadap Slagging Pembakaran Bahan Bakar Jumputan Padat Dengan Penambahan Dolomit - GALIH PRATAMA; Nur Hayati; Trisma Jaya Saputra (UNIB Press, 2026)
This research analyzes the effect of combustion temperature on slagging formation in Solid Refuse-Derived Fuel (SRDF) and evaluates the effectiveness of dolomite additives in mitigating this issue. While SRDF is a promising alternative fuel for co-firing systems, its high ash and alkali metal content often lead to slagging, which can impair combustion performance. The experimental method utilized a muffle furnace with temperature variations of 600°C, 700°C, and 800°C for a duration of 120 minutes. The SRDF samples consisted of an 8:2 ratio of organic to inorganic waste, integrated with 10% dolomite additive based on a 50-gram total sample mass. Observed parameters included slagging mass, slag distribution, and calorific value. The results indicate that temperature significantly influences slagging formation. Furthermore, the addition of dolomite effectively reduces slag formation by increasing the ash fusion temperature through the creation of calcium-based compounds. With the additive, the fuel achieved a calorific value of 4,013.09 cal/g, meeting national (SNI) standards. Ultimately, dolomite proves to be an effective solution for optimizing SRDF utilization as a sustainable energy source in co-firing applications.